Corporate investment in the global financial crisis - Jucá, Michele; Fishlow, Albert (Journal of Business Economics and Management, 2021)
This paper exams the impact of high levels of bank debt, leverage, credit obtained from government banks and cash reserves in the long and short terms investments of firms in the main Latin American countries after this crisis. For this purpose, it is applied a difference-in-differences test in a sample of more than 500 public and private firms, using hand-collected data of firms’ governmental bank dependence. The review period considers five previous (2003–2007) and subsequent years (2008–2012) to the crisis. The major results are reduction of long-term investments for firms with greater banking dependence, as well as short-term investments for firms with a higher level of cash reserves. Besides, firms that are more reliant on government-owned banks reduce capital expenditures. Differently from other studies, this one examines the impact of the last global financial crisis on the firms´ investment, considering its dependence of bank debt of institutions that belongs to the government or not. Understanding the mechanisms available to emerging economies can shed light on new countercyclical policies of governments and changes in the legislations of the financial system.